Práticas de Leitura na Educação de Jovens e Adultos: (re) pensando compreensões e possibilidades para a Escola Técnica de Saúde de Cajazeiras - ETSC - Pereira, Dimas Andriola (2010)
This research has emerged as a requirement to answer experienced uneasiness thereupon working of Programa Nacional de Integração da Educação Profissional com a Educação Básica na Modalidade de Educação de Jovens e Adultos PROEJA, at Instituto Federal de Educação, Ciência e Tecnologia da Paraíba IFPB / Campus de Cajazeiras, regarding the year 2007, according to the stablishments of Enactment nº 5.840, from 13/07/2006. These concerns were outbursts of teachers who affirmed they were not able to proceed faced with the difficulties, on students side, to the comprehension of the contents, much of this critical situation is attributed to the absence of intimacy between students and reading. In this regard our research arose aiming at analyzing reading practices experienced by PROEJA students as a way to understand their formation as a subject-reader. Our work is based on Kleiman (1996), Silva (1995), Orlandi (1996), Soares (2001), Freire (1994) and Foucambert (1989) reading conceptions, theorists whose works are centered on basic and elementary principles about the grasp of reading and writing mechanisms. The observation was carried out in a PROEJA classroom, at da Escola Técnica de Saúde de Cajazeiras, Universidade Federal de Campina Grande, in December 2009 and March 2010. The group was made up of 20 young and adult students and they were chosen by draw, eight of them to an interview. Methodological procedures were conducted on a qualitative research, which in description and analysis offers us a better approach to research subject; semi-structured interviews and data analysis method, following the investigation of interviewees speech, ensuring, in this way, a systematic organization of interviews transcripts, followed by their awareness allied with theoretical discussions about reading. We verified, broadly, students mainly tend to read novels, comics and newspapers. School environment is limited to textbook contents, which do not reach, in most cases, student s reading sensitivity.